Indications for palatal sinus lift: Case series - Amin Rahpeyma; Saeedeh Khajehahmadi (Wolters Kluwer Medknow Publications, 2018)
Background: Open sinus lift is indicated in posterior maxilla when subantral bone is insufficient for insertion of dental implants. Lateral approach is the most used technique. Sometimes, this surgery is difficult due to thick buccal bone or other anatomic variations of maxillary sinus. Aim: The aim of this study was to determine cases that palatal approach open sinus lift is indicated. Settings and Design: This study was a retrospective study. Materials and Methods: Archive files of Dental Implant Department of Mashhad Dental School were searched for palatal sinus lift. The reason for patients was noticed. Pre- and post-operative radiographs were evaluated. Results: Ten patients with palatal approach sinus lift were included. Seven patients had previous insufficient sinus lift, one patient had acute palatonasal recess, and two other patients had thick buccal bone. Conclusion: Palatal approach is maxillary open sinus lift is a useful auxiliary in patients with heavy buccal vestibule scar, thick buccal bone, deep palatonasal recess, and for reentry augmentation.